The Litsea genome and the evolution of the laurel family - Chen, Yi-Cun; Li, Zhen; Zhao, Yun-Xiao; Gao, Ming; Wang, Jie-Yu; Liu, Ke-Wei; Wang, Xue; Wu, Li-Wen; Jiao, Yu-Lian; Xu, Zi-Long; He, Wen-Guang; Zhang, Qi-Yan; et al. (Nature communications, 2020)
The laurel family within the Magnoliids has attracted attentions owing to its scents, variable inflorescences, and controversial phylogenetic position. Here, we present a chromosome-level assembly of the Litsea cubeba genome, together with low-coverage genomic and transcriptomic data for many other Lauraceae. Phylogenomic analyses show phylogenetic discordance at the position of Magnoliids, suggesting incomplete lineage sorting during the divergence of monocots, eudicots, and Magnoliids. An ancient whole-genome duplication (WGD) event occurred just before the divergence of Laurales and Magnoliales; subsequently, independent WGDs occurred almost simultaneously in the three Lauralean lineages. The phylogenetic relationships within Lauraceae correspond to the divergence of inflorescences, as evidenced by the phylogeny of FUWA , a conserved gene involved in determining panicle architecture in Lauraceae. Monoterpene synthases responsible for production of specific volatile compounds in Lauraceae are functionally verified. Our work sheds light on the evolution of the Lauraceae, the genetic basis for floral evolution and specific scents. Litsea cubeba belongs to the Lauraceae family within the Magnoliids clade. Here, the authors assemble its genome and reveal divergence of inflorescence and sexual differentiation, the phylogenetic relationships across the Lauraceae and related species, and biosynthetic genes related to essential oil synthesis.